AB1014 Safety of outpatient percutaneous native renal biopsy in patients with systemic autoimmune diseases: results from a monocentric cohort. (15th June 2017) - Roccatello, D; Sciascia, S; Rossi, D; Naretto, C; Bazzan, M; Solfietti, L; Radin, M; Baldovino, S; Menegatti, E
Abstract : Background: Renal involvement is common in patients with systemic autoimmune conditions, mainly systemic lupus erythematosus (SLE) and vasculitis, including cryoglobulinemia. Despite the advances in percutaneous kidney biopsy (PKB) techniques and overall improved safety of the procedure, clinically significant bleeding complications do occur. Objectives: to investigate the safety of performing percutaneous native kidney biopsy (PKB) as an outpatient procedure (implying an observation period of 6 hrs) compared to the traditional inpatient policy in patients with systemic autoimmune conditions. Methods: Group I, in whom PKB was performed in the outpatient department (2012–2016) and followed by 6 hours' observation period and then by regular outpatient visits and group II, in whom PKB was performed and followed by at least 1-day hospital admission. Group II included retrospectively retrieved patients who underwent PKB in our Institution between January 2000 and November 2012 as in patient procedure. All biopsies were performed by a single nephrologist following a structured protocol. Results: A total of 81 biopsies (group I and group II) were included in this study, 44 (54%) of patients were female and the mean age was 49.9±17.6 years. Twenty-six per cent of biopsies were performed for the diagnostic workup of nephrotic range proteinuria, 21% for rapidly progressive renal insufficiency, and the remaining 53% for non-nephrotic proteinuria and/or hematuria. No patient suffered for a major complication and only 3 (3.7%) patients (one with cryoglobulinemic vasculitis and 2 with ANCA associated vasculits) developed a minor complication, including gross hematuria in one case and sub-capsular perinephric hematoma on sonography not requiring intervention in 2 patients Conclusions: The lack of major complications and the very limited rate of minor bleeding support that outpatient biopsy could be a valuable, safe, and perhaps cost-effective method of obtaining diagnostic renal tissue in the majority of patients with systemic autoimmune diseases. Disclosure of Interest: None declared